Characterization of Cellulose-Producing Bacterial Isolates from the Areca Nut (Areca catechu L.) - Nuryanti, Siska; Herwin, Herwin; hikma, Nurhikma (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Areca nut peel (Arecha catechu L.), a byproduct of areca nut processing, holds potential as a raw material for bioplastics through cellulose utilization. This study aimed to identify bacterial species in areca nut peel capable of producing cellulose. Employing bacterial isolation and identification methods, including morphological and biochemical tests, four bacterial isolates were obtained. Two isolates, identified as gram-negative, were classified under the genus Acetobacter, and two gram-positive isolates were identified as belonging to the genus Lactobacillus. These findings demonstrate the potential use of cellulose from areca nut peel in bioplastic production.